(untitled) (Bangladesh Journal of Agricultural Research, 2012)
Sericulture is a labour intensive agro-based rural industry, which provides periodical income throughout the year. In view of this, it is very much imperative to know the sericulture economics in order to motivate new farmers to take up sericulture and increase their income. Therefore, a study was conducted with the help of personal interview of 70 rainfed sericulture farmers in Udaipur district of Rajasthan, India. The study concluded that in garden establishment, highest share of cost was associated with human labour (INR 14,400.00) followed by that for FYM (INR 2418.75). Similarly human labour (51.93%) accounted for highest element of cost in leaf production activities too owing to high labour wages and shortage of manpower. Labour (25.33%) was second major cost component next to mulberry leaf (38.64%) in silk cocoon production. The average yield of silk cocoon obtained was 1289.04 kg/ha per year. The net return obtained was INR 52039.32 and benefit cost ratio was 1.49. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11176 Bangladesh J. Agril. Res. 37(1): 49-54, March 2012